hutchings-final-sol[1]

# hutchings-final-sol[1] - Answers to Hutchings’ 03 Final...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Answers to Hutchings’ 03 Final Note that you will be expected to provide more detail in your solutions than what is presented below. 1. Let x ( t ) and y ( t ) be the x and y components of r , respectively. Now d dt f ( x ( t ) , y ( t )) = f x ( x ( t ) , y ( t )) x ( t ) + f y ( x ( t ) , y ( t )) y ( t ) Since f x ( x, y ) = ye xy , and f y ( x, y ) = xe xy , d dt f ( x ( t ) , y ( t )) | t =0 = 2 e 1 · 2 (3) + 1 e 1 · 2 (4) = 10 e 2 2. (a) A normal vector to the surface is the gradient of f ( x, y, z ) = x 2 + y 2 + z 2 . ∇ f = h 2 x, 2 y, 2 z i , so a normal at (3 , 2 , 1) is h 6 , 4 , 2 i . (b) A normal vector to the surface at (2 , 1 , 3) is the gradient of f ( x, y, z ) =- x 2 + y 2 + z at the point: h- 4 , 2 , 1 i . Thus, the tangent plane is- 4( x- 2) + 2( y- 1) + 1( z- 3) = 0 3. The only critical point of f is (2 , 0), which lies outside the constraint. We use the method of Lagrange multiplies to check the boundary g ( x, y ) = x 2 + 2 y 2 = 1. From the equation ∇ f = λ ∇ g , and the boundary equation, we get the following three equations to solve: 2 x- 4 = λ (2 x ) (1) 2 y = λ 4 y (2) x 2 + 2 y 2 = 1 (3) From (2), we have that λ = 1 2 , or y = 0. If y = 0, then x = ± 1 by (3). If λ = 1 2 , then x = 4 by (1), so 2 y 2 =- 15, which is a contradiciton. Thus, we only have (1 , 0) and (...
View Full Document

## This note was uploaded on 03/09/2010 for the course PHYSICS 7A taught by Professor Lanzara during the Fall '08 term at Berkeley.

### Page1 / 3

hutchings-final-sol[1] - Answers to Hutchings’ 03 Final...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online